PENERAPAN ARSITEKTUR MULTI-TIER DENGAN DCOM DALAM SUATU SISTEM INFORMASI - Gunadi, Kartika; Julistiono, Irwan Kristanto; Tantama, Heliman Prasetya (Institute of Research and Community Outreach - Petra Christian University, 2001)
Information System implementation using two-tier architecture result lack in several critical issues : reuse component, scalability, maintenance, and data security. The multi-tiered client/server architecture provides a good resolution to solve these problems that using DCOM technology . The software is made by using Delphi 4 Client/Server Suite and Microsoft SQL Server V. 7.0 as a database server software. The multi-tiered application is partitioned into thirds. The first is client application which provides presentation services. The second is server application which provides application services, and the third is database server which provides database services. This multi-tiered application software can be made in two model. They are Client/Server Windows model and Client/Server Web model with ActiveX Form Technology. In this research is found that making multi-tiered architecture with using DCOM technology can provide many benefits such as, centralized application logic in middle-tier, make thin client application, distributed load of data process in several machines, increases security with the ability in hiding data, dan fast maintenance without installing database drivers in every client. Abstract in Bahasa Indonesia : Penerapan sistem informasi menggunakan two-tier architecture mempunyai banyak kelemahan : penggunaan kembali komponen, skalabilitas, perawatan, dan keamanan data. Multi-tier Client-Server architecture mempunyai kemampuan untuk memecahkan masalah ini dengan DCOM teknologi. Perangkat lunak ini dapat dibuat menggunakan Delphi 4 Client/Server Suite dan Microsoft SQL Server 7.0 sebagai perangkat lunak database. Aplikasi program multi-tier ini dibagi menjadi tiga partisi. Pertama adalah aplikasi client menyediakan presentasi servis, kedua aplikasi server menyediakan servis aplikasi, dan ketiga aplikasi database menyediakan database servis. Perangkat lunak aplikasi multi-tier ini dapat dibuat dalam dua model, yaitu client/server windows model dan client/server web model dengan activeX Form teknologi. Pada penelitian ini ditemukan bahwa pembuatan arsitektur multi-tier dengan DCOM teknologi memiliki banyak keuntungan seperti, memusatkan logika aplikasi pada middle-tier, membuat thin client aplikasi, mendistribusikan beban proses data pada beberapa mesin, meningkatkan keamanan dengan kemampuan menyembunyikan data, cepatnya perawatan dengan tanpa instalasi database driver pada setiap client. Kata kunci: multi-tier clien-server, architecture, DCOM, active form.